Bioinspired butterfly wings triboelectric nanogenerator with drag amplification for multidirectional underwater-wave energy harvesting. (1st October 2022) - Wang, Xinxian; Gao, Qi; Zhu, Mingkang; Wang, Jianlong; Zhu, Jianyang; Zhao, Hongwei; Wang, Zhong Lin; Cheng, Tinghai
Graphical abstract: Highlights: A bioinspired butterfly wings triboelectric nanogenerator is designed. Low-frequency wave energy is efficiently harvested by drag amplification. The prototype can harvest multidirectional underwater-wave energy. The prototype immersed in water has excellent durability. Abstract: Underwater-wave energy, as a kind of abundant but neglected renewable energy, is challenging to be efficiently harvested due to the low frequency and random moving direction. In this work, a bioinspired butterfly wings triboelectric nanogenerator (BBW-TENG) is proposed for multidirectional wave energy harvesting from the underwater environment, which is composed of a shell with bionic blades and the generation units. The parameters for the shape and number of blades are analyzed by computational fluid dynamics (CFD) to determine the optimal structural parameters and verify that the bionic blades have the characteristic of drag amplification. What's more, the BBW-TENG responds sensitively to the multidirectional underwater-wave excitation, which demonstrates the ability to harvest multidirectional and low-frequency underwater-wave energy. The output performance of 400 V, 2.9 µA, and 0.31 µC can be generated with the frequency of 1.25 Hz. In practical applications, it is verified that the BBW-TENG can provide power supply for the electronic devices. And the BBW-TENG immersed in water for 45 days indicates excellent durability without diminished electrical performance. Therefore, this work gives a new approach of harvesting underwater-wave energy to long-term power supply for the distributed sensors.